2021
DOI: 10.3390/jcm10122739
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin A1c in Patients with Diabetes Predict Long-Term Mortality Following Coronary Artery Surgery

Abstract: Objective: to estimate the association between preoperative hemoglobin A1c (HbA1c) levels below and above 7%, and the rate of all-cause mortality (ACM) in diabetes mellitus (DM) patients after coronary artery bypass grafting (CABG) within a ten-year follow-up period. Methods: we collected data on patient HbA1c levels that were measured up to 3 months prior to isolated CABG in consecutive patients with DM, and analyzed the rates of ACM over a median of a 5.9-year post-operative period. Results: preoperative HbA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Studies have suggested that a high blood sugar level is an independent predictor of cardiovascular disease regardless of the diagnosis of DM ( 50 52 ). One study suggested that the perception of disease and self-care behaviors were predictive factors significantly associated with the HbA1c level ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that a high blood sugar level is an independent predictor of cardiovascular disease regardless of the diagnosis of DM ( 50 52 ). One study suggested that the perception of disease and self-care behaviors were predictive factors significantly associated with the HbA1c level ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…It can cause postoperative complications such as wound infection, delayed wound healing, and dehydration, highlighting the need for more careful control of blood glucose in these patients . Muhammad Abu Tailakh et al indicated that diabetic patients with ME HbA1c > 7% after elective coronary artery bypass graft surgery had a more 5-year mortality rate than healthy individuals, indicating the importance of long-term blood glucose control to reduce stress-related complications such as heart surgery in diabetic patients [24]. In a study conducted on 409 patients who underwent heart surgery, Gandhi et al showed that per 20 mg of increase in blood glucose above 100 mg during surgery, respiratory and renal complications increase by 30% [25].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the frequency of DM among these patients continues to grow along with an increase in the prevalence of DM among the general population [3]. Since the presence of concomitant DM not only affects the choice of the myocardial revascularization strategy [4,5], but also the prognosis after such interventions [6], attention is now being paid not only to the presence of DM, but also to the degree of glycemic control [7][8][9]. In addition, since even the presence of prediabetes can affect the prognosis in cardiac patients [10], active screening of early carbohydrate metabolism disorders before coronary interventions is justified [11][12][13].…”
Section: Introductionmentioning
confidence: 99%